Subacute Oral Toxicity Study of Arsenic Compound Sameerpannag Rasa in Albino Rats - Swati Ambulkar1 , Pranit Ambulkar2 , Ashish B. Budhrani3 , Manish P. Deshmukh4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Despite the long tradition of thousands of years and acceptance in common public, Ayurvedicmedicines of mercurial, metallic and mineral origin are seen with fear and doubt because in toxicologymercury, metals etc. are known as toxic to the human body. The main reason for dispute lays in the methodof analysis of the Ayurvedic metallic and mercurial medicines. The usual method of analysis of medicinesfor heavy metals is usually atomic absorption spectro-photometry etc. where elements can be detected butthe molecular form is not detected. Arsenic in Sameerpannag Ras is more than a thousand times higherthan the permissible limit of Arsenic in medicines, still successful use of this medicine is Ayurveda practicebrings the hypothesis that it is non-toxic in therapeutic dose.Method: Sameerpannag Ras is a medicinal compound made with three Arsenic ores and Sulphur. Properanimal ethics committee approval was taken, 150 Albino rats were divided into five groups viz control,vehicle control, therapeutic dose, 2X dose and 5X dose. Subacute oral toxicity study was conducted as perOECD guidelines, general behaviours, blood analysis and histopathology study of vital organs were doneto access toxicity.Results: Histopathology study reveals that the consumption of Sameerpannag Rasa in therapeutic dose aswell as in five times the therapeutic dose for 28 days did not cause any significant changes in tissues of liver,kidney, lungs, heart or brain. The behaviour of animals was unchanged during the study, also there was nomortality during the study period.Conclusion: Sameerpannag Ras prepared as per classical Ayurvedic pharmaceutical procedure consumedin therapeutic dose is non-toxic in acute toxicity study. Irrespective of the Arsenic as its major constituent,the pharmaceutical method makes it not-toxic, hence re-establishing its safety and relevance in Ayurvedasystem of medicine.